Effectiveness of the Natura 2000 network for freshwater fish conservation in a Mediterranean region - Gavioli, Anna; Filipe, Ana Filipa; Patonai, Katalin; Milardi, Marco; Castaldelli, Giuseppe (Frontiers in Environmental Science, 2023)
Protected areas (PAs) are the cornerstones of global biodiversity conservation efforts, but to fulfil this role they must be effective at conserving both habitat and species. Among protected taxa, freshwater fish are exposed to multiple disturbances and are considered one of the most endangered. The Nature 2000 reserves network was established with the aim of preserving biodiversity across Europe, but few assessments have been made on its effectiveness on the conservation of freshwater fish species. We tested the hypothesis that fish community is exposed to less anthropogenic pressures within the Nature 2000 sites than outside, hosting a higher number of native species and maintain lower number of non-native species. We tested these hypotheses considering 3777 sampling sites, found across the entire Italian territory. Results showed that PAs did not guarantee less anthropogenic impacts and higher fish species richness than outside PAs, suggesting that PAs are not a panacea for anthropogenic pressures presence and in safeguarding fish diversity. Nevertheless, more caution should be applied to the management measures and the design of new PAs due to the limitations of the protection of a single stretch within a whole river ecosystem. Moreover, the impossibility to operate any management of invasive fish species on the broad scale of a whole river basin, is likely the most limiting factor to fish biodiversity conservation in Italy. Finally, it is also necessary to extend the analysis to other basins and Natura 2000 sites in Europe.